The incidence of microcytosis in the newborn (possible alpha-thalassemia) in the Tabuk region of Saudi Arabia - Özsoylu, Şinasi; Alhejaily, Mohammed (The Turkish Journal of Pediatrics, 1987)
The frequency of microcytosis in the newborn was determined in our study carried out on 69 newborns delivered at Tabuk Maternity and Children's Hospital. Microcytosis, presumed to be associated with alpha thalassemia was documented in at least 11.5% of the subjects by using the Coulter Counter Model M.
Keywords: microcytosis; alpha-thalassemia; Saudi Arabia; newborn